MODEL PERESAPAN AIR HUJAN DENGAN MENGGUNAKAN METODE LUBANG RESAPAN BIOPORI (LRB) DALAM UPAYA PENCEGAHAN BANJIR - Budi, Basuki Setiyo (Politeknik Negeri Semarang, 2013)
Land around building of Materials and Land Laboratory of Civil Engineering Department of Semarang State Polytechnic infrastructure such as roads (asphalt, concrete, paving blocks) and drains an area with impermeable pavement that can not absorb water. Impact when the rainy season occurs puddle on a large scale into the flood, instead of the drought in the dry season due to lack of availability of ground water. To overcome this, the seepage of rain made using the method Biopori Hole Infiltration (LRB). Infiltration pits Biopori a cylindrical hole about 10 cm in diameter is dug into the ground. Depth does not exceed the groundwater table, which is about 100 cm of the soil surface. The hole is filled to the brim organic waste closer to the ground. LRB can increase the ability of soil to absorb water. The water absorption wells that penetrate through the surface of the wall into the soil around the hole LRB. Thus, it will increase the water reserves in the soil. Biopori soil moisture content and moisture content of 85.342% 35.168% native soil. So the water content in the soil biopori greater than the water content in the original soil. Infiltration load will increase in line with increasing hole diameter Biopori infiltration. LRB diameter of 10 cm with a depth of 100 cm using only horizontal surface 79 cm2 produces vertical surface area of 0.314 m2 wall hole, then expand the soil surface can be 40 times the direct contact with the compost. The volume of incoming waste deposited in the pit will reach a maximum of 7.9 liters biodervitas ground through the wall hole, will cause maximum load 25 liter/m2 composting. Land use will affect the power of absorbing soil against rain water. On the ground that a lot of concrete and sealed in a rather dense residential, small power of absorbing soil. This is very different from the conditions in the yard or garden soil that has a power of absorbing up to 100%. Therefore, in the densely populated area needed more LRB to increase the power of absorbing soil.